Foliar Application of Vegetal-Derived Bioactive Compounds Stimulates the Growth of Beneficial Bacteria and Enhances Microbiome Biodiversity in Lettuce - Luziatelli, Francesca; Ficca, Anna Grazia; Colla, Giuseppe; Baldassarre Švecová, Eva; Ruzzi, Maurizio (Frontiers in plant science, 2019)
Many studies on plant biostimulants and organic fertilizers have been focused on the ability of these products to increase crop productivity and ameliorate crop tolerance to abiotic stresses. However, little information is available on their effect on plant microbiota, whereas it is well known that microorganisms associated with plant play crucial roles on the health and productivity of their host. The aim of this study was to evaluate the effect of a vegetal-derived protein hydrolysate (PH), a vegetal-derived PH enriched with copper (Cu-PH), and a tropical plant extract enriched with micronutrients (PE) on shoot growth and the epiphytic bacterial population of lettuce plants and the ability of these products to enhance the growth of beneficial or harmful bacteria. The three plant-derived products enhanced shoot biomass of lettuce plants indicating a biostimulant effect of the products. Data obtained using culture-independent (Terminal Restriction Fragment Length Polymorphism and Next Generation Sequencing) and culture-dependent approaches indicated that foliar application of commercial products altered the composition of the microbial population and stimulated the growth of specific bacteria belonging to , , , and genus. Data presented in this work demonstrated that some of these strains exhibited potential plant growth-promoting properties and/or biocontrol activity against fungi and bacteria phytopathogens including , , and species. No indication of potential health risks associated to the enrichment of human or plant bacterial pathogens emerged by the analysis of the microbiota of treated and no-treated plants. Overall, the findings presented in this study indicate that the commercial organic-based products can enhance the growth of beneficial bacteria occurring in the plant microbiota and signals produced by these bacteria can act synergistically with the organic compounds to enhance plant growth and productivity.